Answer:
[tex]x = 6.75[/tex]
[tex]y = -0.25[/tex]
Step-by-step explanation:
Given :
[tex]x + 3y = 6[/tex] ..................... equation 1
[tex]-x + y = -7[/tex] ................... equation 2
solving the system of equation by substitution method , from equation 1 , make x the subject of the formula , that is
[tex]x = 6 - 3y[/tex] ........................... equation 3
substitute equation 3 into equation 2 , that is
[tex]- ( 6 - 3y) + y = -7[/tex]
[tex]-6 + 3y + y = - 7[/tex]
[tex]-6 + 4y = -7[/tex]
[tex]4y = -7 + 6[/tex]
[tex]4y = -1[/tex]
[tex]y = \frac{-1}{4}[/tex] [tex]= -0.25[/tex]
substitute [tex]y = \frac{-1}{4}[/tex] into equation 3 to find the value of x , that is
[tex]x = 6 - 3 (\frac{-1}{4})[/tex]
[tex]x = 6 + \frac{3}{4}[/tex]
[tex]x = \frac{27}{4}[/tex]
[tex]x = 6. 75[/tex]
Therefore :
[tex]x = 6. 75[/tex]
[tex]y = - 0.25[/tex]